2007
DOI: 10.1007/s10545-007-0449-6
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy depresses total body fat oxidation in the absence of genetic limitations to fat oxidation

Abstract: Cholesterol lowering drugs are associated with myopathic side effects in 7% of those on therapy, which is reversible in most, but not all patients. This study tested the hypothesis that total body fat oxidation (TBFO) is reduced by statins in patients with genetic deficiencies in FO, determined by white blood cells (FOwbc) and by molecular analysis of common deficiencies, and would cause intolerance in some patients. Six patients on statin therapy without myopathic side effects (tolerant) and 7 patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In the present study, the fat oxidation rate was similar between simvastatin-treated patients and control subjects. This is in line with the studies of short treatment (5 days–8 weeks) [ 15 , 16 ], but not those of longer treatment [ 17 19 ]. However, in the long-term studies, it is possible that a different plasma lipid profile [ 17 , 19 ], VO 2 max, or age [ 18 ] between the treatment and control groups may have caused the reported difference in fat oxidation rate.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the fat oxidation rate was similar between simvastatin-treated patients and control subjects. This is in line with the studies of short treatment (5 days–8 weeks) [ 15 , 16 ], but not those of longer treatment [ 17 19 ]. However, in the long-term studies, it is possible that a different plasma lipid profile [ 17 , 19 ], VO 2 max, or age [ 18 ] between the treatment and control groups may have caused the reported difference in fat oxidation rate.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, it has been demonstrated that statins reduce ox-LDL production [38,39], and decrease total body fat oxidation [40]. A study by Van Tits et al [41] reported a decrease of 35-43% in ox-LDL by therapeutic intervention with statins in patients with familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…14 Interestingly, in the latter study, the resting respiratory exchange ratio (RER; an index of fat and carbohydrate metabolism) increased with statin therapy in both asymptomatic and symptomatic statin users, consistent with other reports suggesting that statins decrease or impair fat oxidation. [15][16][17] An altered RER attributable to statins could alter exercise metabolism and diminish aerobic exercise performance.…”
mentioning
confidence: 99%